Description of Stikes Yarsis students' motivation in facing the international nursing job opportunity - Heris Santy, Wesiana (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2012)
The proliferation of nursing higher education in Indonesia increases the number of nurse graduates in Indonesia. Unfortunately, it is not equivalent with the jobs provided for them as well as their low motivation to catch the opportunity to work abroad. Therefore, this research was purposed to describe the motivation of students of Stikes Yarsis in facing the international nursing job opportunity. The type of research was descriptive involving all students of the second and fourth class in the program of study S1 Nursing Stikes Yarsis as the population. The samples were taken from all population by applying the total sampling technique, totally 184 respondents. Moreover, the research variable was the motivation of students of Stikes Yarsis in facing the international nursing job opportunity. The result showed that half of the respondents, 92 students, had a low motivation in facing the international nursing job opportunity. Low motivation is one of the factors which influence the students not to catch the job opportunity abroad. Hence, Stikes Yarsis as the nursing education provider is expected to be able to increase their motivation by giving information, providing facilities which support the students in developing their ability in speaking foreign languages, as well as building networking with institutions outside this country so that the graduates will easily get a job abroad.